Alcohol-induced inhibition of bone formation and neovascularization contributes to the failure of fracture healing via the miR-19a-3p/FOXF2 axis. Issue 6 (20th June 2022) - Zhu, Daoyu; Fang, Haoyu; Yu, Hongping; Liu, Pei; Yang, Qianhao; Luo, Pengbo; Zhang, Changqing; Gao, Youshui; Chen, Yi-Xuan
Abstract : Aims: Alcoholism is a well-known detrimental factor in fracture healing. However, the underlying mechanism of alcohol-inhibited fracture healing remains poorly understood. Methods: MicroRNA (miR) sequencing was performed on bone mesenchymal stem cells (BMSCs). The effects of alcohol and miR-19a-3p on vascularization and osteogenic differentiation were analyzed in vitro using BMSCs and human umbilical vein endothelial cells (HUVECs). An in vivo alcohol-fed mouse model of femur fracture healing was also established, and radiological and histomorphometric analyses were used to evaluate the role of miR-19a-3p. The binding of miR-19a-3p to forkhead box F2 (FOXF2) was analyzed using a luciferase reporter assay. Results: miR-19a-3p was identified as one of the key regulators in the osteogenic differentiation of BMSCs, and was found to be downregulated in the alcohol-fed mouse model of fracture healing. In vitro, miR-19a-3p expression was downregulated after ethanol administration in both BMSCs and HUVECs. Vascularization and osteogenic differentiation were independently suppressed by ethanol and reversed by miR-19a-3p. In addition, the luciferase reporter assay showed that FOXF2 is the direct binding target of miR-19a-3p. In vivo, miR-19a-3p agomir stimulated callus transformation and improved the alcohol-impaired fracture healing. Conclusion: This study is the first to demonstrate that the miR-19a-3p/FOXF2 axis has a pivotal role in alcohol-impaired fracture healing, and may be a potential therapeutic target. Cite this article: Bone Joint Res 2022;11(6):386–397.